Impact of the 0.1% fuel sulfur content limit in SECA on particle and gaseous emissions from marine vessels. (November 2016) - Zetterdahl, Maria; Moldanová, Jana; Pei, Xiangyu; Pathak, Ravi Kant; Demirdjian, Benjamin
Abstract: Emissions were measured on-board a ship in the Baltic Sea, which is a sulfur emission control area (SECA), before and after the implementation of the strict fuel sulfur content (FSC) limit of 0.1 m/m% S on the 1st of January 2015. Prior to January 2015, the ship used a heavy fuel oil (HFO) but switched to a low-sulfur residual marine fuel oil (RMB30) after the implementation of the new FSC limit. The emitted particulate matter (PM) was measured in terms of mass, number, size distribution, volatility, elemental composition, content of organics, black and elemental carbon, polycyclic aromatic hydrocarbons (PAHs), microstructure and micro-composition, along with the gaseous emissions at different operating conditions. The fuel change reduced emissions of PM mass up to 67%. The number of particles emitted remained unchanged and were dominated by nanoparticles. Furthermore, the fuel change resulted in an 80% reduction of SO2 emissions and decreased emissions of total volatile organic compounds (VOCs). The emissions of both monoaromatic and lighter polyaromatic hydrocarbon compounds increased with RMB30, while the heavy, PM-bound PAH species that belong to the carcinogenic PAH family were reduced. Emissions of BC remained similar between the two fuels. This study indicates that the use of low-sulfur residual marine fuel oil is a way to comply with the new FSC regulation and will reduce the anthropogenic load of SO2 emissions and secondary PM formed from SO2. Emissions of primary particles, however, remain unchanged and do not decrease as much as would be expected if distilled fuel was used. This applies both to the number of particles emitted and some toxic components, such as heavy metals, PAHs or elemental carbon (EC). The micro-composition analyses showed that the soot particles emitted from RMB30 combustion often do not have any trace of sulfur compared with particles from HFO combustion, which always have a sulfur content over 1%m/m. The soot sulfur content can impact aging and cloud condensation properties. This study is an in-depth comparison of the impact of these two fuels on the emissions of particles as well as their composition and microstructure. To evaluate the impact of the use of low-sulfur residual marine fuel oils on emissions from ships, additional research is needed to investigate the varied fuel types and compositions as well as the wide range of engine conditions and properties. Graphical abstract: Highlights: Study of the impact of the legislation of fuel sulfur content on emissions to air. Measurements done on the same ship and engine using different marine fuels. Nanoparticles dominated the particle emissions for both fuels. The particle emissions are related to sulfur and other fuel characteristics. Emissions of SOX were reduced with 85% after 2015.